Formaldehyde Gas as a Germicidal and Disinfecting Agent as Employed with the Sanitary Formaldehyde Regenerator (H. K. Mulford Company, 1897)
A brochure about the value of using formaldehyde gas for disinfection measures created by a company that sold formaldehyde regenerators, the instrument used to produce and distribute formaldehyde gas. Includes tables of results from tests of bacteria on different surfaces and formaldehyde gas's effect on the bacteria. The last pages are a price list for sanitary formaldehyde regenerators and a price list for diptheria antitoxic serum, tetanus antitoxin, tuberculin for veterinary tests, and mallein for veterinary tests.
Keywords: Formaldehyde; H. K. Mulford Company; Disinfection and disinfectants--Equipment and supplies; Disinfection and disinfectants